The 3D Stereotaxic Brain Atlas of the Degu With MRI and Histology Digital Model with a Freely Rotatable Viewer - Kumazawa-Manita, Noriko (Brain Science,, 2018)
This is the first digital atlas of the degu brain with microscopic features simultaneously in Nissl sections and magnetic resonance imaging (MRI). As an experimental animal model, the degu contributes to a variety of medical research fields in diabetes, hyperglycemia, pancreatic function, and adaptation to high altitude, among others. Recently the degu has gained increasing importance in the field of neuroscience, particularly in studies evaluating the relationship between sociality and cognitive brain functions, and in studies pertaining to the evolutional aspects of the acquisition of tool-use abilities. Furthermore, aging-related brain dysfunction in humans can be studied using this animal model in addition to mammals with much longer lifespans. This brain atlas is constructed to provide histological and volume-rendered information simultaneously, fitting with any spatial coordination in brain positioning. It can be a useful guide to degus as well as to other rodents for studies of brain structures conducted using MRI or other contemporary examination methods with volume-rendering functions.